IMPLEMENTASI NILAI-NILAI AKHLAK DALAM PEMBELAJARAN AL-QUR'AN DAN HADIS UNTUK MEMBENTUK PROFIL PELAJAR RAHMATAN LIL 'ALAMIN - Imam Anas Hadi; Umi Jamilatus Syukur; Yayah Kurniawati; Agus Budianto (TEACHER : Jurnal Inovasi Karya Ilmiah Guru, 2026)
ABSTRACT The prevalence of bullying, intolerance, and declining mutual respect among students indicates that religious education has not yet fully succeeded in internalizing moral values into students' behavior. This condition highlights the importance of implementing moral values through Qur'an and Hadith learning to support the development of the Rahmatan lil 'Alamin Student Profile. This study aims to describe the implementation of moral values in Qur'an and Hadith learning and to analyze its relationship with the development of the Rahmatan lil 'Alamin Student Profile. The study employed a descriptive qualitative approach using a library research method. Data were collected from official documents issued by the Indonesian Ministry of Religious Affairs and fifteen scientific journal articles, which were analyzed using content analysis techniques. The findings identified four main implementation strategies: integrating moral values into lesson planning, teachers' role modeling (uswah hasanah), habituation of moral values through classroom interactions, and learning based on Qur'anic stories combined with Rahmatan lil 'Alamin Student Profile strengthening projects. The literature review also revealed that these implementation strategies are associated with the strengthening of various dimensions of the Rahmatan lil 'Alamin Student Profile, although their representation across the literature remains uneven. This study suggests that Qur'an and Hadith learning plays a strategic role as a medium for internalizing moral values and strengthening students' character through the synergy of teachers, madrasahs, and families. ABSTRAK Fenomena perundungan, intoleransi, dan menurunnya perilaku saling menghargai di kalangan pelajar menunjukkan bahwa pembelajaran agama belum sepenuhnya mampu menginternalisasikan nilai-nilai akhlak ke dalam perilaku peserta didik. Kondisi ini mendorong pentingnya implementasi nilai-nilai akhlak melalui pembelajaran Al-Qur'an dan Hadis untuk mendukung pembentukan Profil Pelajar Rahmatan lil 'Alamin. Penelitian ini bertujuan mendeskripsikan implementasi nilai-nilai akhlak dalam pembelajaran Al-Qur'an dan Hadis serta menganalisis keterkaitannya dengan pembentukan Profil Pelajar Rahmatan lil 'Alamin. Penelitian menggunakan pendekatan kualitatif deskriptif dengan metode studi kepustakaan. Data diperoleh dari dokumen resmi Kementerian Agama dan lima belas artikel ilmiah yang dianalisis menggunakan teknik content analysis. Hasil penelitian mengidentifikasi empat strategi utama implementasi, yaitu integrasi nilai akhlak dalam perencanaan pembelajaran, keteladanan guru (uswah hasanah), pembiasaan nilai dalam interaksi pembelajaran, serta pembelajaran berbasis kisah Qurani dan proyek penguatan Profil Pelajar Rahmatan lil 'Alamin. Hasil telaah juga menunjukkan bahwa implementasi strategi-strategi tersebut memiliki keterkaitan dengan penguatan berbagai dimensi Profil Pelajar Rahmatan lil 'Alamin, meskipun tingkat kemunculannya dalam literatur belum merata. Penelitian ini menunjukkan bahwa pembelajaran Al-Qur'an dan Hadis memiliki peran strategis sebagai media internalisasi nilai-nilai akhlak yang mendukung penguatan karakter peserta didik melalui sinergi antara guru, madrasah, dan keluarga.